(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article focuses on the upbringing of children, and puppet theater plays an important role in instilling in their minds the concepts of love, good and evil. Because any knowledge and visual impressions received in childhood will remain in the child’s mind for a lifetime.